THE ROLE OF BIG DATA IN THE HEALTHCARE INDUSTRY - Nik Azliza Nik Ariffin; Dr.Alwi Mohd Yunus; Dr.Syamsuriansyah; Dr. Irwan Kamaruddin Abdul Kadir (Journal of Islamic, Social, Economics and Development, 2021)
Big Data in the healthcare industry can contribute to more efficient healthcarebecause it changes the way the patients and doctors in handling care. Healthcare big datarefers to collecting and analyzing the patient's clinical data. Hospital admission statistics andvital statistics registries are the traditional data that has been collected at the population level.Currently, health data are being collected through EMR, social media, mobile phones andmuch more. The increasing establishment of Big Data in healthcare is in response to thedigitization of health information concurrently will encourage the usage of data analytics. Therise of big data means an improvement in the healthcare industry where decision-making is notbased on experience but more on Big Data research.